2013
DOI: 10.1103/physreve.87.052206
|View full text |Cite
|
Sign up to set email alerts
|

Sand dunes as migrating strings

Abstract: We develop a reduced complexity model for three-dimensional sand dunes, based on a simplified description of the longitudinal and lateral sand transport. The spatiotemporal evolution of a dune migrating over a nonerodible bed under unidirectional wind is reduced to the dynamics of its crest line, providing a simple framework for the investigation of three-dimensional dunes, such as barchan and transverse dunes. Within this model, we derive analytical solutions for barchan dunes and investigate the stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…In such conditions, the dune migrates back and forth laterally. The dune sinuosity is then reminiscent of the transverse instability of dunes (Courrech du Pont, ; Guignier et al, ; Parteli et al, ; Reffet et al, ). This instability does not occur in our numerical setup because the sand source maintains the upstream end of the linear dune which does not migrate laterally except at the tip.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In such conditions, the dune migrates back and forth laterally. The dune sinuosity is then reminiscent of the transverse instability of dunes (Courrech du Pont, ; Guignier et al, ; Parteli et al, ; Reffet et al, ). This instability does not occur in our numerical setup because the sand source maintains the upstream end of the linear dune which does not migrate laterally except at the tip.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Parteli et al [] have shown that a transverse dune is globally unstable because a difference in height accelerates the smallest longitudinal dune slice and is then amplified by lateral flows associated with avalanches. In our case, we show that when there is an input sand flux, the overall dispersive flux may be stronger on the windward face than on the lee face [ Niiya et al , ; Guignier et al , ]. This may be an important stabilizing factor which was not taken into account by Parteli et al [].…”
Section: Discussionmentioning
confidence: 99%
“…Floquet stability analysis supplies the natural modes of the perturbation behavior and hence the general stability properties of the system's equilibrium. According to Floquet theory, the fundamental solution operator associated with (11) is introduced as the matrix (t) which is computed by advancing a 5 × 5 identity matrix over one temporal period (from t = 0 to t = T ) according to (11). Each column of (t) is a linearly independent solution of the system.…”
Section: Modal Analysismentioning
confidence: 99%
“…However, it is worth recalling that transverse dunes can decay into a chain of barchans (crescent-shaped dunes) and display a "sea-wave-like" shape with meandering. The formation of barchan dunes is very common and widely studied in an aeolian environment, as demonstrated by a vast body of literature [9][10][11], but has also been detected in subaqueous conditions both in laboratory experiments [12] and in real rivers [13].…”
Section: Introductionmentioning
confidence: 99%